Pelayanan Administrasi Kependudukan Pada Kantor Distrik Merauke - Juventus Bangkit Wibowo; Coleta Maskikit; Adrianus Warman (Jurnal Administrasi Karya Dharma, 2022)
This study aims to determine the Population Administration services carried out at the Merauke District Office, Merauke Regency. The type of research used in this research is descriptive qualitative method, with the research location at the Merauke District Office, Merauke Regency. The focus of this study explains that the quality of service at the Merauke District Office includes several indicators including service procedures, completion time, service costs, service products, infrastructure, and service personnel competence. Data collection techniques used in this riset are interviews, observation, and documentation studies, the data analysis technique used is qualitative data analysis. The results of the study indicate that the implementation of Population Administration Services at the Merauke District Office, Merauke Regency has been running well. Suggestions that can be taken is to further improve services, especially in the field of administration so that people understand better what to bring and complete in the administration of population administration